Outcomes associated with acute kidney disease: a systematic review and meta-analysis. (January 2023) - Su, Ching-Chun; Chen, Jui-Yi; Chen, Sheng-Yin; Shiao, Chih-Chung; Neyra, Javier A.; Matsuura, Ryo; Noiri, Eisei; See, Emily; Chen, Yih-Ting; Hsu, Cheng-Kai; Pan, Heng-Chih; Chang, Chih-Hsiang; et al.
Summary: Background: Acute kidney disease (AKD) defines the period after kidney damage and it is a critical period of both repair and fibrotic pathways. However, the outcomes of patients with AKD have not been well-defined. Methods: In this meta-analysis, PubMed, Embase, Cochrane and China National Knowledge Infrastructure were searched on July 31, 2022. We excluded studies including patients undergoing kidney replacement therapy at enrollment. The data was used to conduct a random-effects model for pool outcomes between patients with AKD and non-AKD (NKD). This study is registered with PROSPERO, CRD 42021271773. Findings: The search generated 739 studies of which 21 studies were included involving 1, 114, 012 patients. The incidence rate of community-acquired AKD was 4.60%, 2.11% in hospital-acquired AKD without a prior AKI episode, and 26.11% in hospital-acquired AKD with a prior AKI episode. The all-cause mortality rate was higher in the AKD group (26.54%) than in the NKD group (7.78%) (odds ratio [OR]: 3.62, 95% confidence interval [CI]: 2.64 to 4.95, p < 0.001, I 2 = 99.11%). The rate of progression to end-stage kidney disease (ESKD) was higher in the AKD group (1.3%) than in the NKD group (0.14%) (OR: 6.58, p < 0.001, I 2 = 94.95%). The incident rate of CKD and progressive CKD was higher in the AKD group (37.2%) than in the NKD group (7.45%) (OR:4.22, p < 0.001, I 2 = 96.67%). Compared to the NKD group, patients with AKD without prior AKI had a higher mortality rate (OR: 3.00, p < 0.001, I 2 = 99.31%) and new-onset ESKD (OR:4.96, 95% CI, p = 0.002, I 2 = 97.37%). Interpretation: AKD is common in community and hospitalized patients who suffer from AKI and also occurs in patients without prior AKI. The patients with AKD, also in those without prior AKI had a higher risk of mortality, and new-onset ESKD than the NKD group. Funding: This study was supported by Ministry of Science and Technology (MOST) of the Republic of China (Taiwan) [grant number, MOST 107-2314-B-002-026-MY3, 108-2314-B-002-058, 110-2314-B-002-241, 110-2314-B-002-239 ], National Science and Technology Council (NSTC) [grant number, NSTC 109-2314-B-002-174-MY3, 110-2314-B-002-124-MY3, 111-2314-B-002-046, 111-2314-B-002-058 ], National Health Research Institutes [PH-102-SP-09 ], National Taiwan University Hospital [109-S4634, PC-1246, PC-1309, VN109-09, UN109-041, UN110-030, 111-FTN0011 ] Grant MOHW110-TDU-B-212-124005, Mrs. Hsiu-Chin Lee Kidney Research Fund and Chi-mei medical center CMFHR11136 . JAN is supported, in part, by grants from the National Institute of Health, NIDDK (R01 DK128208 and P30 DK079337 ) and NHLBI (R01 HL148448-01 ).